Epigenetics and Probiotics Application toward the Modulation of Fish Reproductive Performance - Md Afsar Ahmed Sumon; Mohammad Habibur Rahman Molla; Israa J. Hakeem; Foysal Ahammad; Ramzi H. Amran; Mamdoh T. Jamal; Mohamed Hosny Gabr; Md. Shafiqul Islam; Md. Tariqul Alam; Christopher L. Brown; Eun-Woo Lee; Mohammed Moulay; et al. (Fishes, 2022)
Fish represent an excellent source of animal protein as well as a biomedical research model as a result of their evolutionary relatedness and similarity with the human genome. Commercial and ornamental fish culture has achieved popularity, but reproductive dysfunctions act as a limiting factor for quality fry production, interfering with the sustainability of the aquaculture industry. Fish reproduction is crucial for any species’ existence, and reproductive performance can potentially be improved through applications of epigenetics and probiotics. Epigenetics is a highly sensitive molecular approach that includes chromatin structure and function alteration, DNA methylation, and modification of non-coding RNA molecules for the transfer of desired information from parents to offspring. DNA methyltransferase improves reproductive cyp11a1, esr2b, and figla gene expression and feminizes zebrafish (Danio rerio). Moreover, epigenetics also contributes to genome stability, environmental plasticity, and embryonic development. However, methylation of specific genes can negatively affect sperm quality, resulting in poor fertilization. Probiotic administration is able to induce responsiveness of incompetent follicles to maturation-inducing hormones and can change oocyte chemical composition during vitellogenic development. The positive role of probiotics on testicular cells is validated by upregulating the transcription levels of leptin, bdnf, and dmrt1 genes facilitating the spermatogenesis. This review not only discusses the effects and mechanism of epigenetics and probiotics for improving fish reproduction, but also presents an overview of the causal factors and current techniques used to eradicate dysfunction. Moreover, key genes and hormones related to fish reproduction along with research gaps and future prospects are also considered. This review provides an overview of necessary information for students, scientists, researchers, and breeders to resolve fish reproduction-related problems to ensure profitable and sustainable aquaculture.